Porous clumping non-stick bottom soybean-cassava composite cat litter and preparation method thereof
Patent Information
- Application Number
- CN202610068793.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-19
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-01-19
AI Technical Summary
[0006]为克服上述背景技术中存在的豆腐猫砂结团强度不足、易沾底,木薯猫砂糊化粘附性强、结构稳定性差,以及现有复合猫砂材料中不同组分吸水行为不同步、除臭效果不持久问题,本发明的目的在于提供一种多孔易结团的不沾底豆腐-木薯复合猫砂及其制备方法
[0025]本发明通过将多孔豆腐猫砂颗粒与预糊化木薯猫砂颗粒进行协同复合,使豆腐颗粒的快速吸水与横向扩散作用与木薯淀粉的凝胶结团作用在时间和空间上实现匹配,避免尿液集中渗透至砂盆底部,从结构机理上有效降低结团体与盆底的粘附概率,实现不沾底结团。
Smart Images

Figure CN121647182B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of pet supplies and functional plant-based materials, specifically to a porous, easily clumping, non-stick tofu-cassava composite cat litter and its preparation method. Background Technology
[0002] Cat litter is a common consumable in pet care, and its absorbency, clumping resistance, anti-sticking properties, and odor control directly affect the user experience. Currently available plant-based cat litters mainly include tofu cat litter, cassava cat litter, and their composite materials.
[0003] Several hybrid cat litter solutions have been disclosed in the prior art. For example, patent number CN116171868A, entitled "Hybrid Cat Litter and its Preparation Method," discloses a hybrid cat litter composed of tofu cat litter, PRO-C deodorizing granules, bentonite cat litter, and STA deodorizing agent. This hybrid cat litter improves the absorbency and deodorizing effect of the litter through the combination of multiple functional materials. While this type of hybrid cat litter improves liquid absorption speed and odor adsorption capacity to some extent, the distribution and synergistic effect of the components in the system still have room for further optimization due to differences in the structural morphology, particle size, and water absorption behavior of the different functional particles.
[0004] Furthermore, cat litter materials with cassava starch or its derivatives as the main component are prone to gelatinization after absorbing water. While this helps with clumping, improper control can easily lead to increased localized adhesion, affecting the structural stability of the clumps and ease of cleaning. Meanwhile, existing composite cat litters mostly employ simple physical mixing methods, lacking effective structural synergy between different functional materials. The utilization efficiency of odor-detergent materials and the durability of their deodorizing effect still need improvement.
[0005] Therefore, how to ensure the safety and environmental friendliness of plant-based cat litter, and through reasonable structural design and preparation process, enable different functional components to work synergistically in the processes of water absorption, clumping, and deodorization, thereby simultaneously improving clumping strength, anti-sticking performance, and the stability of deodorization effect, remains a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] To overcome the problems of insufficient clumping strength and easy sticking of tofu cat litter, strong gelatinization and poor structural stability of cassava cat litter, and asynchronous water absorption behavior and short-lasting deodorization effect of different components in existing composite cat litter materials, the present invention aims to provide a porous, easily clumping, non-sticky tofu-cassava composite cat litter and its preparation method. The primary objective of this invention is to overcome the systemic defects caused by material interface incompatibility and mismatch in water-absorbing gel kinetics in existing simple mixed cat litters. It provides a complete technical solution from material selection, ratio optimization, interface control to process structural design, to achieve synergistic improvement in clumping strength, anti-sticking properties, long-lasting deodorization, and usage stability, rather than improvement of a single indicator. This invention employs a composite cat litter system mainly composed of porous tofu cat litter particles, pregelatinized cassava cat litter particles, and modified carbon crystal deodorizing particles. Through a reasonable component ratio design and a preparation method combining stepwise mixing and stepped drying, the porous water-absorbing structure and the starch gel structure form a synergistic effect during water absorption and clumping. Meanwhile, by surface modification of the carbon crystal material, it is directionally distributed in the composite system and exerts a highly efficient and long-lasting deodorizing function. While ensuring that the raw materials used are food-grade, safe, and environmentally friendly, the composite cat litter provided by this invention can form a firmly clumped structure that is not easily adhered to the bottom of the litter box during use, and has a stable and long-lasting deodorizing effect, thereby significantly improving the overall performance of the cat litter product in terms of clumping performance, anti-sticking performance, and overall user experience.
[0007] The objective of this invention can be achieved through the following technical solutions:
[0008] A porous, easily clumping, non-stick tofu-cassava composite cat litter, comprising the following raw materials in parts by weight: 65-70 parts porous tofu cat litter granules; 25-30 parts pregelatinized cassava cat litter granules; and 4-7 parts modified carbon crystal deodorizing granules. The modified carbon crystal deodorizing granules are preferentially loaded onto the surface of the pregelatinized cassava cat litter granules using sodium alginate as a primary binder to form cassava-carbon crystal functional units. These cassava-carbon crystal functional units are then distributed in combination with the porous tofu cat litter granules, enabling the composite cat litter to form a stable clumping structure during water absorption and reducing the adhesion of the clumped groups to the bottom of the litter box.
[0009] Optionally, the weight ratio of porous tofu cat litter granules, pregelatinized cassava cat litter granules, and modified carbon crystal deodorizing granules is 67.40 : 27.30 : 5.30.
[0010] Optionally, the modified carbon crystal deodorizing granules include the following raw materials in parts by weight: 65-75 parts activated carbon; 25-35 parts attapulgite; and 2-5 parts citric acid.
[0011] Optionally, a method for preparing modified carbon crystal deodorizing particles includes the following steps:
[0012] (1) Add activated carbon and attapulgite to water and mix and disperse them to obtain a carbon crystal matrix mixture;
[0013] (2) Add citric acid aqueous solution to the carbon crystal matrix mixture and impregnate it under stirring conditions to load citric acid onto the surface of the carbon crystal matrix;
[0014] (3) The impregnated and modified mixture is subjected to solid-liquid separation and dried under low temperature conditions to obtain modified carbon crystal deodorizing particles.
[0015] Optionally, in step (2), the mass fraction of the citric acid aqueous solution is 2.0% to 5.0%, the impregnation modification is carried out at 20 to 40°C, and the modification time is 30 to 120 min; in step (3), the low-temperature drying is carried out at 50 to 80°C until the mass is constant.
[0016] Optionally, a method for preparing a porous, easily clumping, non-stick tofu-cassava composite cat litter includes the following steps:
[0017] S1, pregelatinized cassava cat litter granules and modified carbon crystal deodorizing granules are mixed in the first stage in the presence of an initial binder to construct a cassava-carbon crystal functional unit.
[0018] S2, porous tofu cat litter particles are added to the cassava-carbon crystal functional unit and a second stage of mixing is carried out in the presence of an interface modifier;
[0019] S3, the mixed materials are subjected to a step-by-step drying and maturation process to obtain a porous, easily clumped, non-stick tofu-cassava composite cat litter.
[0020] Optionally, the mixing conditions in step S1 are: mixing at 20–30°C and a rotation speed of 15–30 rpm for 5–15 minutes; the initial tackifier is an aqueous solution of sodium alginate.
[0021] Optionally, the interface modifier in step S2 is a composite aqueous solution containing polyvinyl alcohol and glycerol.
[0022] Optionally, at the end of the second stage of mixing in step S2, the overall moisture content of the mixture is controlled at 13.0% to 14.0%.
[0023] Optionally, step S3, the stepped drying and maturation treatment, includes drying at 55-65°C for 20-40 minutes and then drying at 45-55°C for 60-120 minutes, so that the resulting composite cat litter, after absorbing urine, forms a clump that can be scooped up as a whole, and a weak bonding interface is formed between the clump and the bottom of the litter box.
[0024] The beneficial effects of this invention are:
[0025] This invention synergistically combines porous tofu cat litter granules with pregelatinized cassava cat litter granules, achieving a temporal and spatial match between the rapid water absorption and lateral diffusion of the tofu granules and the gelation and agglomeration effect of the cassava starch. This prevents urine from concentrating and penetrating to the bottom of the litter box, effectively reducing the probability of the agglomerates adhering to the bottom of the litter box from a structural mechanism perspective, thus achieving non-stick clumping.
[0026] Meanwhile, this invention uses activated carbon-attapulgite composite carbon crystals modified with food-grade citric acid as the deodorizing component. By introducing acidic functional groups on the surface, it improves the selective adsorption capacity for ammonia and sulfur-containing odor molecules, enabling the deodorizing material to play a continuous and stable deodorizing role in cat litter, avoiding the problems of low efficiency and short action time of traditional deodorizing components.
[0027] This invention achieves a synergistic improvement in clumping strength, anti-sticking performance, and deodorization effect without introducing non-degradable mineral materials, solving the technical problem that existing plant-based cat litter struggles to balance clumping and ease of cleaning. Attached Figure Description
[0028] The invention will now be further described with reference to the accompanying drawings.
[0029] Figure 1 A comparison of the infrared spectra of carbon crystal deodorizing particles and modified carbon crystal deodorizing particles;
[0030] Figure 2 A comparison chart showing the results of clumping strength test and anti-sticking performance test of samples with different ratios;
[0031] Figure 3 Comparison of deodorization performance test and clumping stability test results for samples with different ratios;
[0032] Figure 4 A process flow diagram for the preparation of non-stick tofu-cassava composite cat litter. Detailed Implementation
[0033] The present invention will be further described below with reference to specific embodiments. However, the present invention is not limited to the following embodiments. Equivalent adjustments made without departing from the spirit and essence of the present invention should also be considered to fall within the protection scope of the present invention.
[0034] Example 1:
[0035] This embodiment aims to verify the basic feasibility and stability of the composite cat litter of the present invention in terms of clumping, anti-sticking and deodorizing performance when the dosage of each component and the preparation conditions are all taken at the lower limit of the scope defined in the claims.
[0036] S1, Preparation of modified carbon crystal deodorizing particles
[0037] Weigh 65 parts by weight of activated carbon and 25 parts by weight of attapulgite, add them to deionized water, and stir and disperse at room temperature for 20 minutes to obtain a carbon crystal matrix mixture. Add a 2.0% by weight citric acid aqueous solution to the carbon crystal matrix mixture, and stir continuously at 20°C for 30 minutes to impregnate and modify it, so that the citric acid is loaded on the surface of the carbon crystal matrix. Then, the mixture is subjected to solid-liquid separation and dried at 50°C to constant weight to obtain modified carbon crystal deodorizing particles.
[0038] S2, First Stage Mixing: Construction of Cassava-Carbon Crystal Functional Units
[0039] Weigh 25 parts by weight of pregelatinized cassava cat litter granules and 4 parts by weight of the above modified carbon crystal deodorizing granules, add them to the mixing equipment, and mix at 15 rpm. During the mixing process, add 1.0% sodium alginate aqueous solution by atomization. The amount added is 2.0% of the total mass of the pregelatinized cassava cat litter granules and the modified carbon crystal deodorizing granules. Continue mixing for 5 minutes so that the modified carbon crystal deodorizing granules preferentially adhere to the surface of the cassava cat litter granules under the action of the initial binder, forming the initial cassava-carbon crystal functional unit.
[0040] S3, Second Stage Mixing: Interface Modulation and Composite Structure Formation
[0041] 65 parts of porous tofu cat litter granules were added to the cassava-carbon crystal functional unit, and an aqueous solution of an interface modifier was added via atomization. The interface modifier was a composite aqueous solution containing 2.0 wt% polyvinyl alcohol and 1.0 wt% glycerol, and its addition amount was 0.5% of the total mass of all raw materials. The mixture was continued to be mixed at 20 rpm for 5 minutes. At the end of the mixing, the overall moisture content of the mixture was controlled at 13.0% ± 0.5%.
[0042] S4, stepped drying and ripening
[0043] The resulting mixture was dried sequentially at 55℃ for 20 minutes and then at 45℃ for 60 minutes to gradually solidify the interfacial structure formed between particles. The final product had a moisture content of approximately 8.0%. After cooling and sieving, a porous, easily agglomerated, non-stick tofu-cassava composite cat litter was obtained. The process is as follows: Figure 4 As shown.
[0044] Example 2:
[0045] This embodiment aims to verify the comprehensive performance of the composite cat litter of the present invention in terms of clumping strength, anti-sticking performance, and deodorizing effect when the proportions of each component and the preparation conditions are within the recommended range of the claims.
[0046] S1, Preparation of modified carbon crystal deodorizing particles
[0047] Weigh 70 parts by weight of activated carbon and 30 parts by weight of attapulgite, add them to deionized water, and stir and disperse them at room temperature for 30 minutes to obtain a carbon crystal matrix mixture. Add a 3.5% by weight of citric acid aqueous solution to the carbon crystal matrix mixture, and stir and impregnate for 60 minutes at 30°C to allow citric acid molecules to be loaded onto the surface of activated carbon and attapulgite through hydrogen bonding and weak complexation. Then, perform solid-liquid separation on the impregnated and modified mixture, and dry it at 65°C to constant weight to obtain modified carbon crystal deodorizing particles.
[0048] S2, First Stage Mixing: Constructing "Cassava-Carbon Crystal Functional Units"
[0049] Weigh 27 parts by weight of pregelatinized cassava cat litter granules and 5 parts by weight of the above modified carbon crystal deodorizing granules, add them to a low-speed drum mixer, and mix at 22 rpm. During the mixing process, slowly add a 1.0% sodium alginate aqueous solution by atomization, the amount of which is about 2.0% of the total mass of the cassava granules and carbon crystal granules, and continue mixing for 10 minutes. Through the above operation, the modified carbon crystal deodorizing granules are preferentially attached to the surface and convex shape of the cassava cat litter granules under the action of sodium alginate as a primary binder, forming a "cassava-carbon crystal functional unit" with a stable coating structure.
[0050] S3, Second Stage Hybridization: Interface Control and Overall Structure Construction
[0051] 67 parts of porous tofu cat litter particles were added to the first mixture, and an interface modifier solution was added by atomization. The interface modifier solution was a composite aqueous solution containing 2.0 wt% polyvinyl alcohol (polyvinyl alcohol 1788) and 1.0 wt% glycerol, and its addition amount was 0.5% of the total mass of all raw materials. The mixing speed was adjusted to 28 rpm and mixing was continued for 12 min. During this mixing stage, the polyvinyl alcohol-glycerol system formed a flexible polymer transition layer at the contact interface between the tofu particles and the "cassava-carbon crystal functional unit" under the action of shear force, realizing the interface compatibility and stress buffering between heterogeneous particles. At the end of the mixing, the overall moisture content of the entire material system was controlled at 13.5% ± 0.5%. This moisture content range is the balance point between interfacial film formation and particles maintaining a free flow state.
[0052] S4, stepped drying and ripening treatment
[0053] The resulting mixture was spread evenly to a thickness not exceeding 3 cm, and the following drying steps were performed sequentially: First stage drying: drying at 60℃ for 30 min to quickly remove free water and preliminarily shape the particle surface; Second stage drying: the temperature was lowered to 50℃ and drying continued for 90 min to further solidify the polyvinyl alcohol interfacial film, while promoting moderate retrogradation of cassava starch and enhancing the stability of the agglomeration structure; After drying, the final moisture content of the material was stably controlled at 9.0% to 10.0%, and after cooling and sieving, a porous, easily agglomerated, non-stick tofu-cassava composite cat litter product was obtained.
[0054] Example 3:
[0055] This embodiment aims to verify the structural stability and applicability of the composite cat litter of the present invention under conditions of high clumping strength and high deodorization capacity when the proportions of each component and the preparation conditions are taken to the upper limit of the allowable range of the claims.
[0056] S1, Preparation of modified carbon crystal deodorizing particles
[0057] Weigh 75 parts by weight of activated carbon and 35 parts by weight of attapulgite, add them to deionized water, and stir and disperse them at room temperature for 40 minutes to obtain a carbon crystal matrix mixture. Add a 5.0% by weight of citric acid aqueous solution to the mixture, and stir continuously at 40°C for 120 minutes to impregnate and modify it, so that the citric acid is fully loaded on the surface of the carbon crystal matrix. Then, the mixture is separated into solid and liquid phases and dried at 80°C to constant weight to obtain modified carbon crystal deodorizing particles.
[0058] S2, Phase 1 Hybridization: Construction of High-Loaded Cassava-Carbon Crystal Functional Units
[0059] Weigh 30 parts by weight of pregelatinized cassava cat litter granules and 7 parts by weight of the above modified carbon crystal deodorizing granules, add them to a mixing device, and mix at 30 rpm; add 1.5 wt% sodium alginate aqueous solution by atomization, the amount of which is 2.5% of the total mass of the two, and continue mixing for 15 min, so that the modified carbon crystal deodorizing granules form a high-coverage functional unit structure on the surface of the cassava cat litter granules;
[0060] S3, Second-stage mixing: Interface-enhanced composite
[0061] 70 parts of porous tofu cat litter granules were added to the functional unit, and an aqueous solution of an interface modifier was added via atomization. The interface modifier was a composite aqueous solution containing 2.5 wt% polyvinyl alcohol and 1.5 wt% glycerol, and its addition amount was 0.8% of the total mass of the raw materials. The mixture was continued to be mixed at 35 rpm for 20 minutes. At the end of the mixing, the overall moisture content of the mixture was controlled at 14.0% ± 0.5%.
[0062] S4, stepped drying and ripening
[0063] The mixture was first dried at 65°C for 40 minutes, and then dried at 55°C for 120 minutes to fully solidify the polymer film formed by the interface modifier. The final product moisture content was controlled at about 12.0%. After cooling and sieving, the high-strength composite cat litter product was obtained.
[0064] Comparative Example 1:
[0065] This comparative example aims to verify the impact of carbon crystal deodorizing particles without citric acid modification on the deodorizing performance and overall performance of composite cat litter.
[0066] S1, Preparation of carbon crystal deodorizing particles
[0067] Weigh 70 parts of activated carbon and 30 parts of attapulgite clay by weight, add them to deionized water, and stir and disperse them at room temperature for 30 minutes to obtain a carbon crystal matrix mixture. Do not add citric acid aqueous solution or perform impregnation modification treatment. Then, perform solid-liquid separation on the mixture and dry it at 65°C to constant weight to obtain unmodified carbon crystal deodorizing particles.
[0068] S2, Simple Mixing
[0069] Weigh 27 parts by weight of pregelatinized cassava cat litter granules and 5 parts by weight of the above unmodified carbon crystal deodorizing granules, add them directly to the mixing equipment, and mix at 22 rpm for 10 minutes; do not add sodium alginate or other primary binders during the mixing process, so that the carbon crystal deodorizing granules are randomly dispersed among the cassava cat litter granules.
[0070] S3, direct compound mixing
[0071] 67 parts of porous tofu cat litter granules were added to the resulting mixture and mixed for 12 minutes at 28 rpm. During this mixing process, no polyvinyl alcohol, glycerin or other interface modifiers were added. The three types of granules were macroscopically mixed only by mechanical mixing. After mixing, the overall moisture content of the material was about 10% to 11%, and no moisture content control was performed for interfacial film formation.
[0072] S4, Single-stage drying
[0073] The resulting mixture was continuously dried at 55°C for 90 minutes until the moisture content was approximately 10%. After cooling and sieving, a comparative cat litter was obtained.
[0074] Comparative Example 2:
[0075] This comparative example aims to verify the effect of not introducing organic small molecule glycerol during the preparation process on the clumping strength, anti-sticking performance, and overall performance of the composite cat litter.
[0076] S1, Preparation of modified carbon crystal deodorizing particles
[0077] Weigh 70 parts of activated carbon and 30 parts of attapulgite clay by weight, add them to deionized water, and stir and disperse them at room temperature for 30 minutes; add 3.5% citric acid aqueous solution, stir and impregnate at 30°C for 60 minutes; then perform solid-liquid separation and dry at 65°C to constant weight to obtain modified carbon crystal deodorizing particles.
[0078] S2, First Stage Mixing: Construction of Cassava-Carbon Crystal Functional Units
[0079] Weigh 27 parts by weight of pregelatinized cassava cat litter granules and 5 parts by weight of the above modified carbon crystal deodorizing granules, add them to a mixing device, and mix at a speed of 22 rpm; add 1.0% sodium alginate aqueous solution by mass through atomization, the amount of which is 2.0% of the total mass of the two, and continue mixing for 10 minutes to form a cassava-carbon crystal functional unit.
[0080] S3, Phase Two Hybrid
[0081] 67 parts of porous tofu cat litter granules were added to the functional unit, and an aqueous solution of an interface modifier containing only 2.0 wt% polyvinyl alcohol and no glycerin was added by atomization. The amount added was 0.5% of the total mass of the raw materials. The mixture was continued to be mixed at 28 rpm for 12 minutes. At the end of the mixing, the overall moisture content of the material was controlled at about 13.5%.
[0082] S4, stepped drying and ripening
[0083] The mixture was first dried at 60°C for 30 minutes, and then dried at 50°C for 90 minutes. The final product had a moisture content of about 10%, which yielded a comparative cat litter.
[0084] Performance testing:
[0085] 1. Method for testing clumping strength
[0086] Cat litter samples obtained from Examples 1, 2, and 3, as well as Comparative Examples 1 and 2, were selected and evenly spread in standard litter boxes of the same size. Under identical environmental conditions, an equal volume of simulated cat urine was slowly added to the surface of each sample, allowing it to be naturally absorbed and clump together. After clumping, the samples were left to stand for a specified time. The clumps were then removed entirely using a litter scoop, and their integrity and resistance to breakage were observed by manually lifting, moving, and gently shaking them. The difference in clumping strength between the examples and the comparative examples was evaluated by comparing the degree of breakage and stability of the clumps during handling.
[0087] 2. Test method for anti-staining performance
[0088] Cat litter samples from Examples 1-3, Comparative Examples 1 and 2 were taken and placed in smooth plastic litter boxes of the same material and size. The same volume of simulated cat urine was added to the designated locations in the litter. After clumping and settling, the litter was scraped off from the edge of the clumping using a litter scoop. The separation of the clumping from the bottom of the litter box was observed, and any obvious adhesion, residue, or need for scraping to remove it was recorded. The anti-sticking performance of each sample was evaluated by comparing the ease with which clumping was removed from different samples.
[0089] 3. Deodorization performance test method
[0090] Equal amounts of cat litter samples from Examples 1, 2, and 3, as well as Comparative Examples 1 and 2, were weighed and placed in separate, sealed test containers. Ammonia sources under identical conditions were introduced into the containers to simulate the odor environment generated during cat litter use. Each container was placed under the same temperature conditions, and changes in odor within the containers were observed and recorded at set time points. The differences in deodorization performance between the examples and the comparative examples were evaluated by comparing the odor reduction effects of different samples under the same conditions and their stability over time.
[0091] 4. Agglomeration stability test method
[0092] Under simulated real-world usage conditions, the cat litter samples from Examples 1-3, as well as Comparative Examples 1 and 2, underwent repeated liquid addition and cleaning operations. Each time, the same volume of simulated cat urine was added, and after clumping, the litter was cleaned using a litter scoop. The clumps were observed to exhibit edge breakage, overall disintegration, or significant pulverization during scooping, movement, and repeated operations. The clumping stability of different samples during long-term use was comprehensively evaluated by assessing whether the clumps remained intact after multiple consecutive tests.
[0093] Table 1 Performance Test Results
[0094] Example 1 9.8 3.5 82 88 Example 2 12.6 0.8 93 96 Example 3 11.2 1.6 89 92 Comparative Example 1 7.1 6.9 63 72 Comparative Example 2 5.4 12.8 51 60
[0095] As shown in Table 1, different samples exhibit a clear and stable performance gradient distribution in terms of clumping strength, anti-sticking performance, deodorization effect, and clumping stability. Among them, the overall performance of the examples is significantly better than that of the comparative samples, and Example 2 achieves the best results in all test indicators, fully demonstrating the advantages of the present invention in terms of component ratio and process synergy.
[0096] Regarding cluster strength, the cluster strength of Example 2 reached 12.6 N, significantly higher than that of Example 1 (9.8 N) and Example 3 (11.2 N), while the cluster strengths of Comparative Example 1 and Comparative Example 2 were only 7.1 N and 5.4 N, respectively. It can be seen that the example samples exhibit stronger structural integrity during stress and transport, while the comparative examples, lacking key modifications or small organic molecule regulation, showed significantly insufficient cluster strength and were prone to breakage.
[0097] Regarding the anti-sticking performance, Example 2 exhibited the lowest sticking rate at only 0.8%, significantly better than Examples 1 and 3, and far lower than Comparative Example 1's 6.9% and Comparative Example 2's 12.8%. This result indicates that the embodiments of the present invention effectively reduce the tendency of clumping to adhere to the bottom of the litter box through the synergistic effect of the porous structure and gel structure, while the comparative sample showed a significantly aggravated sticking problem due to insufficient interface control.
[0098] Regarding deodorization performance, Example 2 achieved an ammonia removal rate of 93% under 12-hour conditions, the highest among all samples. Examples 1 and 3 also achieved ammonia removal rates of 82% and 89%, respectively, both significantly higher than Comparative Example 1 and Comparative Example 2. In particular, Comparative Example 1, which did not undergo carbon crystal modification, showed a significant decrease in deodorization performance, indicating that the citric acid-modified carbon crystal deodorizing particles play a crucial role in improving the deodorization effect in the system of this invention.
[0099] Regarding clumping stability, Example 2 achieved a clumping integrity rate of up to 96% after multiple cleanings, significantly better than Examples 1 and 3. In contrast, the comparative sample showed a substantial decrease in clumping integrity rate after multiple uses, indicating poor structural stability under actual repeated use conditions. Therefore, the embodiments of the present invention can maintain stable clumping morphology and a good user experience even during long-term use.
[0100] In summary, the embodiments of the present invention are significantly superior to the comparative examples in all performance indicators. Furthermore, Example 2 achieves the best performance in terms of clumping strength, anti-sticking performance, deodorization effect, and clumping stability, which fully demonstrates the rationality and superiority of the component ratio and preparation process, and reflects the significant improvement in comprehensive performance of the technical solution of the present invention.
Claims
1. A porous, easily clumping, non-stick tofu-cassava composite cat litter, characterized in that, The composite cat litter comprises the following raw materials in parts by weight: 65-70 parts porous tofu cat litter granules; 25-30 parts pregelatinized cassava cat litter granules; and 4-7 parts modified carbon crystal deodorizing granules. The modified carbon crystal deodorizing granules are preferentially loaded onto the surface of the pregelatinized cassava cat litter granules using sodium alginate as a primary binder to form cassava-carbon crystal functional units. These cassava-carbon crystal functional units are then compounded and distributed with the porous tofu cat litter granules. The sodium alginate primary binder is an aqueous solution of sodium alginate. The preparation method of the composite cat litter includes the following steps: S1, pregelatinized cassava cat litter particles and modified carbon crystal deodorizing particles are mixed in the presence of an initial binder to construct a cassava-carbon crystal functional unit; S2, porous tofu cat litter particles are added to the cassava-carbon crystal functional unit and mixed in the presence of an interface modifier to construct a second stage; S3, the mixed material is subjected to a step-by-step drying and maturation treatment to obtain a porous, easily agglomerated, non-stick tofu-cassava composite cat litter. The first stage of mixing includes adding the pregelatinized cassava cat litter granules and the modified carbon crystal deodorizing granules into a mixing device for mixing. During the mixing process, the sodium alginate primary binder is added by atomization, so that the modified carbon crystal deodorizing granules preferentially adhere to the surface of the pregelatinized cassava cat litter granules under the action of the sodium alginate primary binder, forming a preliminary cassava-carbon crystal functional unit. The second stage of mixing includes adding porous tofu cat litter particles to the cassava-carbon crystal functional unit and adding an interface modifier by atomization. The interface modifier is a composite aqueous solution containing polyvinyl alcohol and glycerin. The step-by-step drying and curing process in S3 includes drying at 55-65℃ for 20-40 minutes, and then drying at 45-55℃ for 60-120 minutes. This process ensures that the resulting composite cat litter, after absorbing urine, forms clumps that can be scooped up as a whole, and that a weak bonding interface is formed between the clumps and the bottom of the litter box.
2. The porous, easily clumping, non-stick tofu-cassava composite cat litter according to claim 1, characterized in that, The weight ratio of the porous tofu cat litter granules, pregelatinized cassava cat litter granules, and modified carbon crystal deodorizing granules is 67.40:27.30:5.
30.
3. A porous, easily clumping, non-stick tofu-cassava composite cat litter according to claim 1 or 2, characterized in that, The modified carbon crystal deodorizing granules comprise the following raw materials in parts by weight: 65-75 parts activated carbon; 25-35 parts attapulgite; and 2-5 parts citric acid.
4. A porous, easily clumping, non-stick tofu-cassava composite cat litter according to any one of claims 1 to 3, characterized in that, The modified carbon crystal deodorizing particles include the following steps: (1) Add activated carbon and attapulgite to water and mix and disperse them to obtain a carbon crystal matrix mixture; (2) Add citric acid aqueous solution to the carbon crystal matrix mixture and impregnate it under stirring conditions to load citric acid onto the surface of the carbon crystal matrix; (3) The impregnated and modified mixture is subjected to solid-liquid separation and dried under low temperature conditions to obtain the modified carbon crystal deodorizing particles.
5. The porous, easily clumping, non-stick tofu-cassava composite cat litter according to claim 4, characterized in that, In step (2), the mass fraction of the citric acid aqueous solution is 2.0% to 5.0%, the impregnation modification is carried out at 20 to 40°C, and the modification time is 30 to 120 min; in step (3), the low temperature drying is carried out at 50 to 80°C until the mass is constant.
6. The preparation method of a porous, easily clumping, non-stick tofu-cassava composite cat litter according to claim 1, characterized in that, The mixing conditions in step S1 are: mixing at 20-30°C and a rotation speed of 15-30 rpm for 5-15 minutes.
7. The preparation method of a porous, easily clumping, non-stick tofu-cassava composite cat litter according to claim 1, characterized in that, When the second stage of mixing in step S2 is completed, the overall moisture content of the mixture is controlled at 13.0% to 14.0%.
Citation Information
Patent Citations
Mixed cat litter and preparation method thereof
CN116171868A
Bamboo-wood sawdust pet clustering padding material and preparation method thereof
CN105594603A
Plant mixed cat litter
CN116406624A
Method for preparing cattle bed padding from cow dung
CN120458019A
Toilet sand for pet, and toilet for pet
JP2008118897A
